Pengaruh Metode Pembelajaran Dan Kecerdasan Sosial Terhadap Hasil Belajar Pendidikan Kewarganegaraan Siswa MAN Tanah Jambo Aye - Fitriani - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
This study aims to discover the correlation of learning methods and social intelli- gence of students’ learning outcomes in citizenship course. There are two learning methods used in this study; collaborative and problem solving, and social intelegence is classi ed into low and high.The results of study: (1) collaborative learning method is better rather than problem solving; (2) there is an interaction between learning method and social intelli- gence in its in uence on learning performancefor citizenship education; (3) students learn- ing resulting collaborative, who have high social intelligence,are greater than problem solving; and (4) low social intelegence students, there was no difference learning results by collaborative or problem solving either.